Acceptability of the Cytosponge procedure for detecting Barrett's oesophagus: a qualitative study. Issue 3 (1st March 2017) - Freeman, Madeleine; Offman, Judith; Walter, Fiona M; Sasieni, Peter; Smith, Samuel G
Abstract : Objective: To investigate the acceptability of the Cytosponge, a novel sampling device to detect Barrett's oesophagus (BE), a precursor to oesophageal adenocarcinoma (EAC), among people with risk factors for this condition. Design: A qualitative study using semistructured interviews and focus group discussions. Data were explored by three researchers using thematic analysis. Setting: Community setting in London, UK. Participants: A recruitment company identified 33 adults (17 men, 16 women) aged 50–69 years with gastro-oesophageal reflux disease (GERD), a risk factor for BE. The majority of participants were white British (73%). The focus groups were stratified by gender and education. 10 individuals were interviewed and 23 participated in four focus groups. Results: 3 key themes emerged from the data: the anticipated physical experience, preferences for the content of information materials and comparisons with the current gold-standard test. Overall acceptability was high, but there was initial concern about the physical experience of taking the test, including swallowing and extracting the Cytosponge. These worries were reduced after handling the device and a video demonstration of the procedure. Knowledge of the relationship between GERD, BE and EAC was poor, and some suggested they would prefer not to know about the link when being offered the Cytosponge. Participants perceived the Cytosponge to be more comfortable, practical and economical than endoscopy. Conclusions: These qualitative data suggest the Cytosponge was acceptable to the majority of participants with risk factors for BE, and could be used as a first-line test to investigate GERD symptoms. Concerns about the physical experience of the test were alleviated through multimedia resources. The development of patient information materials is an important next step to ensuring patients are adequately informed and reassured about the procedure. Patient stakeholders should be involved in this process to ensure their concerns and preferences are considered. Trial registration number: ISRCTN68382401 ; pre-results.